Imatinib in Refractory Crohn Disease: A Series of 6 Cases. Issue 3 (24th September 2019) - Boctor, Anna; Hugot, Jean-Pierre; Leblanc, Thierry; Martinez-Vinson, Christine; Allez, Matthieu; Bellaïche, Marc
Abstract: Biologics have revolutionized Crohn disease (CD) treatment. Nevertheless, absence or loss of response is frequent and alternative therapeutic options may be necessary. Imatinib is a tyrosine kinase inhibitor that is used in chronic myeloid leukemia. A positive impact on CD in 2 patients with chronic myeloid leukemia treated with imatinib led us to propose the drug in 4 additional patients with refractory CD. Four out of these 6 patients reached clinical and endoscopic remission at a median time of 3 months. Remission was maintained for 9 months to 7 years. Imatinib may thus be considered as new therapeutic options for refractory CD. We report 6 CD patients treated with imatinib. Two of them because of a leukemia and 4 because of a disease refractory to all medical options. Four patients experienced full and sometimes prolonged remission of their digestive disease. Lay Summary: Six Crohn's Disease patients have been treated with imatinib, a drug used for hematologic (blood) disorders. Four of them experienced a benefit, sometimes for several years. Imatinib was usually well tolerated.